Antibacterial Testing of Moringa oleifera L. Fruit Extract Against The Growth of The Bacteria Staphylococcus aureus - Anisa Febriani; Agriana Rosmalina Hidayati; Dewi Suryani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Staphylococcus aureus is one of the pathogenic bacteria that causes infectious diseases in humans. Controlling infections caused by pathogenic bacteria can be done by developing new antibacterial agents derived from natural plant-based medicines. Moringa oleifera L is a medicinal plant used in traditional medicine and has antibacterial activity. This study aims to determine the secondary metabolites content and antibacterial activity of Moringa fruit extract against the growth of Staphylococcus aureus bacteria. Moringa fruit simplicia was dechlorophyllated using n-hexane, then extracted using the sonication method with 70% ethanol solvent. The results of the phytochemical screening were that the ethanol extract of Moringa fruit contained flavonoid, tannin and saponin compounds. The diameter of the inhibition zone at concentrations of 25%, 50% and 75% were 1.17 mm, 2.00 and 6.00 mm respectively. Based on the description above, it can be concluded that Moringa fruit extract has the potential to be an antibacterial agent.